As representações sociais dos alunos da licenciatura em matemática sobre a profissão docente - Roma, José Eduardo (2010)
This study seeks to analyze the Social Representations of the Students in the Mathematics Licensing Course regarding the Educational Profession. This thesis was oriented by the questions: What are the representations that these students make about the profession, about being a Mathematics professor? What are the students representations of the Mathematics course regarding the selection process of their future profession? The objective of the study: to analyze how these students represent their future profession, as well as to identify the representations about the formative situations experienced during the course. The theoretical references are based on Moscovici, Jodelet, Farr, Durkheim and Sá to discuss the Social Representations; in Gonçalves and Gonçalves, Fiorentini, Tardif, Pimenta, Shulman, Darling- Hammond and Baratz-Snowden for the formation and know-how; in Popkewitz, Bourdoncle, Imbérnon, Lüdke and Boing to discuss the educational profession; in Sacristán, Contreras, Ramalho, Nunes and Gauthier to discuss the concept of professionality ; and in Cunha, Hypolito, Roldão, Nóvoa, Veiga, Araujo and Kapuzinial, the concepts of professionalism and professionalization. The subjects of the study were students of three Mathematics licensing courses in the countryside of the State of São Paulo, one of which is a Public institution, one is Private and one is a Confessional. The study was developed in two phases. Firstly, the data was collected by applying a questionnaire, adapted from the International Center of Studies in Social Representations and Subjectivity Education (ICSSRS-Ed) and subsequently followed by semi-structured group interviews with the students of the three institutions. The study indicated that the images that the students represented about the future profession are anchored in their penchant for it, by family influence, model or anti-model professors; as well as the search for the articulation of pedagogic and specific disciplines with a practical and supervised internship, and in the new tendencies in mathematics education, in human formation, and in a good relationship. Noted also, were the different roles of the professor which oscillate from political to that of father, monk, counselor and the representation of the profession as a talent, its social importance set against work conditions. Conclusions included the need for new curricular designs, new teaching organization and strengthening of formation projects that can favor the educational profession and stimulate the young to seek it. This study seeks to contribute to the emergence of actions that clearly demonstrate the valorization of the profession, as an incentive to a longer formation process in Licensing Courses; which result in greater integration between them and the schools where the future professor will teach and result in greater awareness of the teacher educator relative to his role in the formation of young professors and, above all, result in an awareness relative to better work conditions at the schools